Penjatuhan Hukuman di Bawah Ancaman Pidana Minimum terhadap Pelaku Tindak Pidana Korupsi Pemerasan oleh Pegawai Negeri Sipil (PNS) di Pelabuhan Kelas III Larantuka Nusa Tenggara Timur : (Studi Kasus: Putusan Pengadilan Negeri Kupang Nomor 17/Pid.Sus-TPK/2017/Pn.Kpg) (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to analyze the imposition of penalties under the minimum criminal threat against perpetrators of corruption extortion by civil servants (PNS) at the Class III port of Larantuka, East Nusa Tenggara (Case study: Kupang District Court Decision Number 17/Pid.Sus-Tpk/2017/Pn.Kpg). This research is a normative juridical research which means that the author does not use samples and data collection is carried out by the library method, with the object of study. After the data is obtained, the author will analyze juridically normative data obtained on the object of study. The corruption case of I Wayan Adisucipto SN was proven to have violated Article 12 letter e Jo Article 12 A of Law No. 31 of 1999 jo Law No. 20 of 2001 concerning Eradication of Corruption, which states a maximum of 20 years in prison or life imprisonment and a minimum of 4 years, but in reality the judge imposed a prison sentence of only 5 months, the decision imposed by the judge that is not considered according to / based on the law will be null and void. The imposition of a 5-month sentence for the defendant by the judge in Number: 17/Pid.Sus-Tpk/2017/Pn.Kpg is not in accordance with the punishment system. From this research, the author can conclude that the Judge's consideration is not based on the provisions of the legislation, namely Article 12 letter e jo Article 12 A Paragraph (2) of Law No. 31 of 1999 Jo Law No. 20 of 2001 concerning Eradication of Corruption which is a minimum imprisonment of at least 4 (four) years and a maximum of 20 (twenty) years so that it is contrary to the applicable law.